IMPLEMENTASI BIMBINGAN KONSELING DALAM PEMBINAAN AKHLAK DI SMP ISLAM INTEGRAL LUQMAN 02 BATAM - Khaerana Nurul Shobrina; Imam Syafi’i; Atik Rusdiani (UNISAN JURNAL, 2025)
The main objective of this study is: to find out the process of implementing counseling guidance in fostering student morals. This research is descriptive qualitative. The method used in this study is a qualitative descriptive research, namely to find out the description of the school which includes guidance and counseling services carried out by counseling teachers. The data sources taken were primary data and sekundary. Results of the study The process of guidance and counseling services carried out by counseling teachers runs effectively..